Tandem arrangement of tubulin genes in the protozoan parasite Leishmania enriettii. - Landfear, S M (1983)
The arrangement of developmentally regulated alpha- and beta-tubulin genes has been studied in the parasitic protozoan Leishmania enriettii by using Southern blot hybridization analysis. The alpha-tubulin genes occur in a tandem repeat whose monomeric unit may be represented by a 2-kilobase PstI fragment. Similarly, the beta-tubulin genes probably occur in a separate tandem repeat consisting of approximately 4-kilobase units unlinked to the alpha-tubulin repeats.